Nilai dan Pesan Moral Tarling Menurut Perspektif Pelaku Kesenian Tarling Cirebon: Studi Psikologi Budaya - Rijal Abdillah; koentjoro koentjoro (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
The purposes of this research were to analyze deeply the values and moral message ofTarling in subject perspective ofTarling-Cirebon Art and performers internalization of value and moral message Tarling. The purpose of this research aimed to answer the research question, how a value and moral message according to the subject perspective of Tarling-Cirebon art and performers internalization of value and moral message Tarling? This research is based on an qualitative study. Subjects perspective of value and moral message in Tarling Art were gathered through observations, interviews, and documentation. The analyzing of internalization process of value and moral message was inspired by ethnography. The result of this study indicate that the values of tarling obtained are empathy of subjects in tarling, covering